El Practicum en las Diplomaturas de Biblioteconomía y Documentación españolas - Chain Navarro, Celia; Muñoz Cañavate, Antonio; BLANCO FAURA, Irene (Revista General de Información y Documentación, 2009)
This article presents the main results of a study aimed at knowing the type of centres where the students of Practicum in the Librarianship and Information Science studies in Spain do their work experiences. The authors have worked with the list of work experiences on offer not with the centres that are assigned to each student. We can conclude that the centres in which the habitual and traditional tasks in our profession carried out are libraries and archives. Moreover the centres and tasks arising of the new professions, for example the web content and the work in enterprises heardly appear.
Keywords: Practicum; Work experience; Laboral market; Librarianship and Information Science Studies; Student